2008
DOI: 10.4142/jvs.2008.9.3.219
|View full text |Cite
|
Sign up to set email alerts
|

All blood, No stool: enterohemorrhagic Escherichia coli O157:H7 infection

Abstract: Enterohemorrhagic Escherichia coli serotype O157:H7 is a pathotype of diarrheagenic E. coli that produces one or more Shiga toxins, forms a characteristic histopathology described as attaching and effacing lesions, and possesses the large virulence plasmid pO157. The bacterium is recognized worldwide, especially in developed countries, as an emerging food-borne bacterial pathogen, which causes disease in humans and in some animals. Healthy cattle are the principal and natural reservoir of E. coli O157:H7, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 150 publications
(197 reference statements)
1
48
1
1
Order By: Relevance
“…According to the stepwise evolutionary model for O157:H7 (8), strain G5101 was thought to be a precursor of SOR Ϫ , GUD Ϫ O157:H7 strains (9). It was previously assumed that clinical O157:H7 isolates carry a virulence plasmid resembling pO157 (24,30). However, in this study we showed that O157:H7 strains could carry virulence plasmids other than pO157.…”
Section: Discussioncontrasting
confidence: 47%
“…According to the stepwise evolutionary model for O157:H7 (8), strain G5101 was thought to be a precursor of SOR Ϫ , GUD Ϫ O157:H7 strains (9). It was previously assumed that clinical O157:H7 isolates carry a virulence plasmid resembling pO157 (24,30). However, in this study we showed that O157:H7 strains could carry virulence plasmids other than pO157.…”
Section: Discussioncontrasting
confidence: 47%
“…EHEC strains are typically known for their ability to produce Shiga toxin and to induce A/E lesions in the host's gut epithelium. While these strains are pathogenic for humans, they can reside peacefully as reservoirs of infection in many production animal types including cattle, swine, and poultry (197). Disease outbreaks in humans are usually associated with the ingestion of some type of food product such as undercooked beef, fresh vegetables, unpasteurized milk and cider, and salami.…”
Section: Ehec and Stec Virulence Plasmidsmentioning
confidence: 99%
“…EHEC strains are a subset of Shiga toxin-producing E. coli (STEC) strains responsible for hemorrhagic colitis (HC) and hemolytic-uremic syndrome (HUS) in humans (197). Although E. coli strains of several serogroups are members of the EHEC pathotype, E. coli strains of the O157 serogroup are responsible for the most severe cases of these diseases (91,128).…”
Section: Ehec and Stec Virulence Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…A major and natural reservoir of Escherichia coli O157:H7 is healthy cattle ( Yoon andHovde 2008, Whitworth et al 2010). According to studies conducted both in Poland, the United Kingdom and the United States, Escherichia coli O157 isolation frequency from cattle is 0.…”
Section: Introductionmentioning
confidence: 99%